A novel time-variant prediction model for megawatt flexible wind turbines and its application in NTM and ECD conditions. (August 2022) - Li, Zhiguo; Gao, Zhiying; Chen, Yongyan; Zhang, Liru; Wang, Jianwen
Abstract: Dynamic response analysis for large-scale horizontal axis wind turbine(HAWT) plays a pivotal role in the design, stability, performance and safety. To overcome the problem of difficult measurement caused by many influence factors in wild wind field, accurately calculate the unsteady load, modal characteristics and dynamic response for megawatt flexible wind turbine components under various complex wind conditions, a novel time-variant prediction model is proposed in the manuscript. It perfectly combines the TUDK (Technical University of Denmark) dynamic inflow aerodynamic model, the hybrid beam theory considering shear deformation and centrifugal stiffening effect and Lanczos decoupling technology widely used in finite element software. Meanwhile, the rotor dynamic inflow effect, structural-damping and aerodynamic-damping of blade and tower, the structural coupling between blade and tower are considered in the model. Furthermore, the time-variant dynamic responses of blade tip and tower top under normal turbulence model (NTM) and extreme coherent gust with direction change (ECD) are further analyzed. The research results under ECD condition are compared with the experimental data from National Renewable Energy Laboratory (NREL) to validate the model accuracy. Graphical abstract: Image 1